ALK Is a Specific Diagnostic Marker for Inflammatory Myofibroblastic Tumor of the Uterus. (October 2018) - Mohammad, Nissreen; Haimes, Josh D.; Mishkin, Skyler; Kudlow, Brian A.; Leong, May Ying; Chew, Sung Hock; Koay, Eleanor; Whitehouse, Ann; Cope, Nichola; Ali, Rola H.; Köbel, Martin; Stewart, Colin J.R.; et al.
Abstract : Inflammatory myofibroblastic tumor (IMT) is a myofibroblastic/fibroblastic neoplasm of intermediate malignant potential. It is frequently characterized by genetic fusion of ALK with a variety of partner genes, which results in the activated ALK signaling pathway that can be targeted with kinase inhibitors. IMTs can occur in the gynecologic tract, with the uterus (corpus and cervix) being the most frequent site. Recent studies suggest that IMTs in the gynecologic tract are underrecognized, and a low-threshold for performing ALK immunohistochemistry has been proposed. The aim of this study was to evaluate the specificity of ALK immunohistochemistry for IMTs among uterine mesenchymal and mixed epithelial/mesenchymal tumors. We performed ALK immunohistochemistry on 14 molecularly confirmed uterine IMTs and 260 other uterine pure mesenchymal and mixed epithelial/mesenchymal tumors. Cases showing any positive cytoplasmic and/or membranous staining of the tumor cells were considered to be ALK positive. All 14 IMTs were confirmed to harbor ALK genetic fusion by RNA sequencing, and ALK immunostaining in the form of granular cytoplasmic positivity with paranuclear accentuation was observed in all 14 cases. ALK was negative (complete absence of staining) in all the other pure mesenchymal tumors and in all mixed epithelial/mesenchymal tumors examined. Our findings show that ALK is a highly specific diagnostic immunohistochemical marker for ALK fusion in uterine mesenchymal tumors. In the work-up of uterine mesenchymal tumors, particularly smooth muscle tumors showing myxoid stromal changes, a diagnosis of IMT should be strongly considered if ALK positivity is observed.